PENGARUH INDEPENDENSI DAN PROFESIONALISME AUDITOR TERHADAP KUALITAS AUDIT DENGAN FEE AUDIT SEBAGAI VARIABEL MODERASI (Studi Empiris pada Kantor Akuntan Publik di Semarang) - Sadewa Sapta Kusuma; Tri Jatmiko Wahyu Prabowo (Diponegoro Journal of Accounting, 2019)
This research was conducted with the aim of examining the role of audit fees in moderating the effect of auditor independence and professionalism on audit quality. The sample used in this research is the auditor who works in the public accounting firm in Semarang. The number of samples received as respondents is 50 samples. Research data was obtained by giving questionnaires to respondents to then be answered. Determination of this sample was carried out by convenience sampling method. The research hypothesis cites using analysis of multiple regression analysis with Ordinary Least Square (OLS) and moderated regression analysis. The results of this research indicate that independence has a positive and significant effect on audit quality while professionalism has no effect on audit quality. In addition, audit fees do not strenghten the effect of auditor independence and professionalism on audit quality.